Penggunaan Media Pembelajaran Interaktif Berbasis Web dalam Pembelajaran Prakarya - Ine Nurul Qomariya; Suraini Suraini; Ansori Ansori (Jurnal Wahana Literasi Pendidikan, 2026)
This study was motivated by the development of educational technology, which has encouraged the use of web-based interactive learning media in the learning process, particularly in craft subjects that require creativity, visualization, and active student engagement. The study was conducted because conventional learning methods were considered less effective in creating engaging and flexible learning experiences for students. This research aims to describe students’ experiences, teachers’ perceptions, and the meaning of using web-based interactive learning media in craft learning at SMA Negeri Grujugan. This study employed a qualitative research design with a phenomenological approach. Data were collected through observation, semi-structured interviews, and documentation. The research participants consisted of craft subject teachers and students who were involved in the use of web-based learning media. The findings revealed that the use of web-based interactive learning media was able to enhance students’ learning motivation, active participation, creativity, and independent learning through engaging and flexible multimedia features. Teachers also expressed positive perceptions regarding the implementation of web-based learning media, as it was considered effective in creating a more efficient and student-centered learning environment. However, the implementation of web-based learning media still encountered several challenges, including limited internet connectivity, insufficient data quotas, and distractions that affected students’ learning focus. Therefore, the use of web-based interactive learning media plays an important role in improving students’ learning experiences and supporting the digital transformation of learning in craft education.